A scaled down laboratory experiment of cross-borehole pulse radar signatures for detection of a terminated tunnel. (1st August 2016) - Cho, Jae-Hyoung; Jung, Ji-Hyun; Kim, Se-Yun; Yook, Jong-Gwan
Abstract: In the cross-borehole pulse radar signatures measured near the front end of a terminated tunnel, the time-of-arrival (TOA) with fully penetrated tunnel is significantly shortened due to the relatively fast pulse propagation in an empty tunnel compared with the TOA obtained without a tunnel. To analyze the TOA variation with the protrusion length of the terminated tunnel from the line-of-sight between two antennas or boreholes, additional borehole pairs are required around the terminated tunnel in spite of their high construction costs. As an alternative, a laboratory scaled down experiment, which has a high ability to simulate different underground configurations, is designed for investigation into the TOA effects of tunnel termination. A round ceramic rod with a careful selection of its dielectric constant is immersed in pure water in a water tank and used to simulate the tunnel in the experiment. Coaxial fed dipole antennas with balanced wire and ferrite cores are used not only to suppress borehole-guided waves but also to generate a symmetric radiation pattern. The accuracy of the laboratory scaled down experiment is verified by the symmetricity of the measured diffraction pattern of the fully penetrated ceramic rod. Then, the TOA variation is measured for the protrusion length of the ceramic rod relative to the line-of-sight between two antennas from +80 mm to −80 mm with an equal step of 5 mm. Based on the scaled down experimental measurements of the TOA, it is found that a tunnel 1.2 m away from the measuring cross-borehole section closely approaches the scaled up variation curve under the same conditions of the protrusion length.